Recovery of germanium from synthetic leach solution of zinc refinery residues by synergistic solvent extraction using LIX 63 and Ionquest 801 - Sankum Nusen (2018)
© 2014 Published by Elsevier B.V. All rights reserved. A synergistic solvent extraction (SSX) system consisting of LIX 63 and Ionquest 801 was identified and developed to recover germanium from a synthetic leach solution of zinc refinery cementation residues. A significant synergistic effect was identified with this novel SSX system, which selectively extracted germanium over other metals in the synthetic leach solution. The SSX system consisting of 0.13 M anti-oxime from LIX 63 and 0.13 M Ionquest 801 in ShellSol 2046 is an optimised composition for the extraction of germanium from the synthetic leach solution containing 1 g/L Ge(IV) and 1.0 M H2SO4. The germanium(IV) extraction kinetics was slow with the equilibrium reached after 20 min of mixing at 40 °C. The stripping kinetics of germanium(IV) with strip solution containing 0.5 M NaOH and 1.0 M Na2SO4was very fast with the equilibrium reached in 1 min of mixing. Slope analysis showed that, most possibly, the extracted Ge(IV)-organic species is 2Ge(SO4)2·(HA)·(HB)2·H2SO4via a solvating mechanism with the SSX system consisting of Ionquest 801 (HA) and LIX 63 (HB).